Comparative efficacy and acceptability of nonpharmacological interventions for sleep disturbance among pregnant women: protocol for a systematic review and network meta-analysis - Nan Zhang; Yi Zeng; Mei Sun; Siyuan Tang; Xiangmin Tan; Qingyi Wu (BMJ Open)
Introduction Sleep disturbance is prevalent in pregnancy and can result in significant adverse outcomes for women and their infants. Numerous clinical trials of various nonpharmacotherapies for preventing or treating sleep disturbances have been conducted previously; however, previous systematic reviews with direct comparisons have failed to demonstrate the best options for different kinds of treatments. This systematic review and network meta-analysis (NMA) aims to explore the comparative efficacy and acceptability of nonpharmacological interventions for sleep disturbances in pregnancy and to assist clinical decision-making through ranking interventions concerning critical clinical outcomes.Methods and analysis We will follow the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) statement. Two reviewers will systematically search five major bibliographic databases (PubMed, Embase, Cochrane Library, Web of Science and Cumulative Index to Nursing and Allied Health Literature) and registries for published and unpublished randomised controlled trials (RCTs) of any nonpharmacological interventions for sleep disturbances from inception to 24 June 2025. To ensure the search is up to date, we will also perform an updated search up to the time of final analysis submission. Primary outcomes will consider efficacy (the overall mean change of any predefined sleep disturbances, including sleep quality, sleep duration and sleep-specific symptoms) and acceptability (all-cause discontinuation). The risk of bias of each included RCT will be assessed using the Cochrane Risk of Bias 2.0 Tool (RoB2). Traditional pairwise meta-analyses and NMAs will be performed to compare the efficacy and acceptability of different nonpharmacological interventions. Surface under the cumulative ranking curve for the outcomes of interest will be used to rank the competing interventions. The Grading of Recommendations, Assessment, Development and Evaluation system will be used to assess the quality of evidence associated with the main results.Ethics and dissemination This review is a secondary analysis of published data and, therefore, does not require ethical approval. The results will be disseminated in a peer-reviewed journal.PROSPERO registration number CRD42024546340.